Tradition of the night Lailatul Qadar During Pandemic - Gian Nitya Putri; Busro Busro (UIN Sunan Gunung Djati Bandung, 2022)
One of the activities carried out as a tradition in the holy month of Ramadan is chasing the night of lailatul qadar at the Hidayatul Believer Mosque. This activity is carried out by the people of the Purbasari village. The enthusiasm of the residents in increasing their worship in the month of Ramadan has made the interest and enthusiasm of the residents in carrying out this activity continue to increase from various ages. The existence of obstacles and obstacles that have occurred in recent times does not break the existence of the tradition of pursuing the night of lailatul qadar. This research was conducted with the aim of discussing the strategy of maintaining the existence of the tradition of pursuing the night of lailatul qadar at the Hidayatul Mukmin mosque, Purbasari Village. The research method used is qualitative through literature study and field observation. The research discussion includes: pursuing the night of lailatul qadar in the Hidayatul Mukmin mosque, I'tikaf as a tradition, and strategies for surviving the pandemic. From this discussion, it can be concluded that in pursuing the night of lailatul qadar, the people of the Purausari village carry out I'tikaf activities on the last 10 nights in the month of Ramadan. The activities carried out are in the form of multiplying prayers, doing praises in the form of shalawat to Allah and His Messenger, multiplying recitations of the Qur'an, asking for forgiveness, and praying at night in congregation. Despite being faced with a pandemic, the existence of this tradition continues in the conventional way. The strategy taken to maintain Itikaf activities to pursue the night of lailatul qadar in a pandemic situation is by being aware of phenomena that occur by recognizing what are the causes, symptoms and how to overcome the disease.